Aplikasi model berbasis masalah dalam membaca bahasa Prancis bagi mahasiswa - Diana Rosita (Aksara: Jurnal Bahasa dan Sastra, 2022)
The problem’s discussion of this research is comparing the application of Problem Based Learning Model (PBL) with conventional teaching in learning achievement of French reading skill for students of first semester students of French education program of Faculty of Teacher Training and Education of Lampung University in academic year 2015/2016. The purpose of this research is to know or describe (1) level in reading ability of French, (2) difference of median score of French reading skill’s achievement of the students who are taught by problem based learning with conventional teaching. The method of this research is used an experimental method. By knowing the hypothesis, the researcher uses t-test formula. To get the data of French reading skill, the researcher is used a test measurement. The result of the data analysis is as follow: 1) the population comes from the students of the first semester. Sampling technique will be used lottery technique, from the population of normal distribution and has homogeneous variety, 2) proposed hypothesis “Median achievement score of French reading skill of the students who are taught by problem based learning model is higher than median achievement score of French reading skill achievement of students who are taught by conventional teaching”, 3) level of reading skill of French student’s achievement in French education program of Faculty of Teacher Training and Education of Lampung University in academic year 2015/2016 is considered to be good, with a median score 75 and 4) the result of this research with the population of Fench education program of Faculty of Teacher Training and Education , first semester in academic year 2015/2016. The hypothesis is accepted if sign more than α. In this case, the significance level is 0.05, meaning only 5% are error and 95% correct. Keywords : problem based learning, French reading skill.